Shifting Sands: Science Researchers on Google Scholar, Web of Science, and PubMed, with Implications for Library Collections Budgets. - Christy Hightower; Christy Caldwell (Issues in Science and Technology Librarianship, 2010)
Science researchers at the University of California Santa Cruz were surveyed about their article database use and preferences in order to inform collection budget choices. Web of Science was the single most used database, selected by 41.6%. Statistically there was no difference between PubMed (21.5%) and Google Scholar (18.7%) as the second most popular database. 83% of those surveyed had used Google Scholar and an additional 13% had not used it but would like to try it. Very few databases account for the most use, and subject-specific databases are used less than big multidisciplinary databases (PubMed is the exception). While Google Scholar is favored for its ease of use and speed, those who prefer Web of Science feel more confident about the quality of their results than do those who prefer Google Scholar. When asked to choose between paying for article database access or paying for journal subscriptions, 66% of researchers chose to keep journal subscriptions, while 34% chose to keep article databases. [ABSTRACT FROM AUTHOR]